Corazón pintado con crayón. Producción de Cortometraje animado en 2D. - Araujo Jiménez, Walter Javier (2014)
This project contains the production process of a digitally animated short film in two dimensions. "Crayon painted heart" is titled. The story unfolds in a children microuniverse classified within the genre of romantic comedy, but its construction and its influences are marked by various genres. The illustration style in the same way contains influences from different styles like manga, and cartoon web series. Production takes place holistically, from the idea and construction of the story to end the post production, being ready for broadcast. It has been experienced in certain stages of it without neglecting the technical criteria required the animation process. Likewise evidenced aesthetic considerations that give meaning to the film. Finally, it is our aim to contribute to the production of animated film in our country. Tags.